Circular RNAs: Methods and Protocols - Dieterich, Christoph; Papantōnēs, Akēs (Methods in Molecular Biology, 2018)
Detection and Reconstruction of Circular RNAs from Transcriptomic Data -- Deep Computational Circular RNA Analytics from RNA-seq Data -- Genome-wide circRNA Profiling from RNA-seq Data -- Analysis of Circular RNAs using the Web Tool CircInteractome -- Characterization and Validation of Circular RNA and their Host Gene mRNA Expression using PCR -- Detecting Circular RNAs by RNA Fluorescence In Situ Hybridization -- Single Molecule Fluorescence In Situ Hybridization (FISH) of Circular RNA CDR1as -- A Highly-efficient Strategy for Overexpressing circRNAs -- Constructing GFP-based Reporter to study Back-splicing and Translation of Circular RNA -- Northern Blot Analysis of Circular RNAs -- Non-radioactive Northern Blot of circRNAs -- Characterization of Circular RNA Concatemers -- Characterization of Circular RNAs (circRNA) Associated with the Translation Machinery -- Synthesis and Engineering of Circular RNAs -- Preparation of Circular RNA in vitro -- Discovering circRNA-microRNA Interactions from CLIP-Seq Data -- Identification of circRNAs for miRNA Targets by Argonaute2 RNA Immunoprecipitation and Luciferase Screening Assays. .